Abu Raykhan Beruni And His Scientific-Spiritual Heritage - Laziza Alidjanova; Ibrohim Nigmatullayev (International Scientific and Current Research Conferences, 2020)
The article provides information regarding to the life and activity of Abu Raykhan Beruni, an analysis of his works, the importance of his scientific-spiritual heritage in the development of science and its significance today.